Individualised funding and its implications for the skills and competencies required by disability support workers in Australia. (2nd January 2019) - Moskos, Megan; Isherwood, Linda
ABSTRACT: Within Australia, the National Disability Insurance Scheme (NDIS) has been heralded as one of the most significant social policy initiatives of recent times. The introduction of the NDIS follows similar moves towards individualised funding and consumer-directed care in the aged care sector. International evidence provides examples of the implications of individualised funding for workers within the social care sector; however, little attention has been paid to how the shift to individualised funding impacts on the skills and competencies required by disability support workers and in an Australian context. Our study aims to provide such an examination. We use qualitative data from in-depth interviews with key stakeholders including disability support workers; people with disability, and their families and carers; disability service providers; and training providers to investigate the impact of the NDIS on the skills and competencies required by disability support workers. Findings suggest that disability support workers require new skills to support choice and control, to be more customer-orientated and, to move from task-focused to person-centred care. As a consequence of these changes, the training of disability support workers is adapting to take account of these new skills and competencies.